2015
DOI: 10.1017/jwe.2014.41
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Wine-Tasting Results and Randomness with a Mixture of Rank Preference Models

Abstract: Evaluating observed wine-tasting results as a mixture distribution, using linear regression on a transformation of observed results, has been described in the wine-tasting literature. This article advances the use of mixture models by considering that existing work, examining five analyses of ranking and mixture model applications to non-wine food tastings and then deriving a mixture model with specific application to observed wine-tasting results. The mixture model is specified with Plackett-Luce probability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 20 publications
0
22
0
Order By: Relevance
“…Equation 2expresses L MLE using a Plackett-Luce rank preference model of each taster's scores. Among many applications, Plackett-Luce was employed to evaluate taste test results for sushi by Chen (2014), animal feed by Marden (1995) and wine by Bodington (2015aBodington ( , 2015b. Plackett-Luce employs a preference probability for each wine (r i for wine i taster t and totals of W wines and T tasters) that expresses the chance that the wine is most-preferred among the alternatives.…”
Section: Description Of the Wop Challengementioning
confidence: 99%
See 1 more Smart Citation
“…Equation 2expresses L MLE using a Plackett-Luce rank preference model of each taster's scores. Among many applications, Plackett-Luce was employed to evaluate taste test results for sushi by Chen (2014), animal feed by Marden (1995) and wine by Bodington (2015aBodington ( , 2015b. Plackett-Luce employs a preference probability for each wine (r i for wine i taster t and totals of W wines and T tasters) that expresses the chance that the wine is most-preferred among the alternatives.…”
Section: Description Of the Wop Challengementioning
confidence: 99%
“…None of the 1328 wines in the 2016 Challenge were assigned the same score by all of the six or seven of the judges who evaluated each wine. Cao (2014) and Bodington (2012Bodington ( , 2015aBodington ( , 2015b posited that observed scores are a mixture of consensus, idiosyncratic and random expressions of preference. Numerous evaluations showed that there is often a consensus among some judges that some wines are better than others.…”
Section: Dispersion Of Scores and Potential Randomness In Awardsmentioning
confidence: 99%
“…are required for formal statistical answers according to the Journal of Wine Economics [1]. In the past decade, many researchers focused on these problems with small to medium sized wine datasets [2][3][4][5]. However, to the best of our knowledge, no research is being performed on analyzing the consistency of wine judges with a large-scale dataset.…”
Section: Introductionmentioning
confidence: 99%
“…Cao (2014) applied a mixture model with random-ranking and consensus-ranking components to the results of the 2009 California State Fair Commercial Wine Competition. Bodington (2015) applied a mixture of rank-preference models to the ranks assigned by experienced tasters during a blind tasting of Pinot Gris, and the results implied that common-preference agreement among tasters exceeded the random expectation of illusory agreement.…”
Section: Introductionmentioning
confidence: 99%
“…The mixture of Plackett-Luce models applied to ranked data for a tasting of Pinot Gris in Bodington (2015) is summarized in Section II. Transforming numerical scores into ranks and choice axioms are discussed in Section III, and an addition to the mixture model to handle ties between numerical scores appears in Section IV.…”
Section: Introductionmentioning
confidence: 99%